'From pregnancy, baby and beyond' – evaluation of a peer support programme for pregnant women living with HIV. (18th April 2012) - Knudsen-Strong, E; Namiba, A; Fraser, S; Johnson, M; Wright, A
Abstract : Introduction: In the last two decades, clinical advancements have repositioned pregnancy as a safe option for women living with HIV. The introduction of services tailored specifically to support HIV-positive women in pregnancy is now both relevant and critical. In response to this need, the London-based organisation 'Positively UK' developed the 'From Pregnancy, to Baby and Beyond' programme, (FPBB), whereby health professionals train 'mentor mothers' to provide peer support. Methodology: A qualitative mixed-methods approach was used to evaluate the programme. Data was collected from a series of 18 semi-structured interviews and 1 focus group with programme clients, mentor mothers, and healthcare providers. Thematic network analysis was conducted, from which two levels emerged – firstly, the exploration of needs of HIV-positive pregnant women, and secondly, the impact of programme participation on the woman and her pregnancy. The impact of women's programme participation was examined in terms of six psychosocial resources, drawing upon the "AIDS-competent community" framework (1). Results: In its pilot phase, the programme achieved six key outcomes in the form of psychosocial resources that promote the health of HIV positive pregnant women: Building knowledge and skills Provision of safe social spaces Promotion of acceptance and proactive responses Developing confidence in strengths Building solidarity Developing partnerships across sectors Conclusion: This preliminary evaluation illustrates the effectiveness of a model combining education and tailored peer support to complement clinical care for pregnant women living with HIV. Further work is underway to look at other outcome measures of programme participation.